2017
DOI: 10.1002/mnfr.201600488
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of VEGF signaling in a mouse model of diabetes by xanthohumol and 8‐prenylnaringenin: Unveiling the angiogenic paradox and metabolism interplay

Abstract: Beer polyphenols modulate T2DM angiogenic paradox in a tissue-dependent manner. We also show for the first time that both polyphenols decreased VEGF-B pathway, which is implicated in endothelial-to-tissue lipid metabolism. Altogether, the effects of these polyphenols in the crosstalk between angiogenesis and metabolism render them potent agents for novel diabetic therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…In recent years, XN ( 1 ), IX ( 2 ) and 8-PN ( 4 ) have been extensively tested for their anti-diabetic properties [ 96 , 134 , 135 ]. Costa et al tested XN ( 1 ) and 8-PN ( 4 ) in a mouse model and found that both compounds have the potential for therapeutic intervention in diabetics type 2 [ 134 ].…”
Section: Phytoestrogensmentioning
confidence: 99%
“…In recent years, XN ( 1 ), IX ( 2 ) and 8-PN ( 4 ) have been extensively tested for their anti-diabetic properties [ 96 , 134 , 135 ]. Costa et al tested XN ( 1 ) and 8-PN ( 4 ) in a mouse model and found that both compounds have the potential for therapeutic intervention in diabetics type 2 [ 134 ].…”
Section: Phytoestrogensmentioning
confidence: 99%
“…In vivo studies: Costa et al, reported that XN consumption 10 mg/l reduced angiogenesis, vascular endothelial growthfactor receptor (VEGFR)-2 expression and activity, and also reduced levels of VEGF-B and its receptors (i.e. VEGFR1 and neuropilin-1), VEGF-A as well as endothelial markers in T2DM mice [39]. Altogether, these findings suggest that XN may have a preventative effect on neovascularisation and the associated pathways seen as complications in T2DM.…”
Section: Xanthohumol and Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…Adipose tissue is highly vascularized in which the adipocytes are nourished by an extensive capillary network [5][6][7]. Expansion of adipogenesis requires angiogenesis [5], whereas, inadequate angiogenesis or vascular dysfunction is closely associated with many metabolic disorders [8][9][10].…”
Section: Introductionmentioning
confidence: 99%